IMPLIKATUR UNGKAPAN BAHASA DAERAH DALAM GUGATAN PENGHINAAN DAN PENCEMARAN NAMA BAIK DI NTT: SEBUAH STUDI KASUS LINGUISTIK FORENSIK - Salimulloh Tegar Sanubarianto (Haluan Sastra Budaya, 2021)
Trends in lawsuits against violations of UU ITE relate to insults and defamation have increased significantly in the past three years, not least in NTT. Some of the cases in the lawsuit included regional expressions. One of them is the case of UU ITE with the decision number 84/Pid.Sus/2019/PN Olm. With the method of in-depth and documentative interviews, this study aims to reveal the implicature in the subject matter text through the Frank Parker implicature disclosure approach. The result showed that the motivation of speaker using local language expressions can be revealed through direct, indirect, and literal speech acts. In literal speech act, speech and implications have not negation. In direct speech act, speakers have implications to advise speech partners. Whereas indirect speech acts, speakers have implications to threaten the speech partners. The conclusion of this study indicate that local languages are effectively used to touch the personal identity of the speech partner so that they are often used to insult and defame.